Motivation and job satisfaction of health workers in a specialized health institution in Serbia - Djordjević, Dragan B; Petrović, Dejan; Vuković, Dejana; Mihailović, Dobrivoje; Dimić, Aleksandar (Vojnosanitetski pregled, 2015)
Background/Aim. Health care system is specific for each country, and therefore involves different motivation and job satisfaction factors. The aim of this study was to confirm the validity and applicability of the General Nordic Questionnaire translated into Serbian for analyzing motivation and job satisfaction, as well as to analyze the motivation factors and job satisfaction of health workers at the Institute for Treatment and Rehabilitation “Niška Banja”. Methods. The General Nordic Questionnaire was translated into Serbian. It included 73 questions (5 answers by the Likert scale), which formed 24 scales. In May, 2012, 196 (82.3%) health workers filled in the questionnaire. Results. A correlation of Ceronbach’s alpha values between the Scandinavian study results and the results of Serbian study was statistically significant (r = 0.424; p < 0.05). The lowest Cronbach’ alfa coefficient was for the scale “learning demand in job demands” (alpha 0.28). The other scale with no satisfactory reliability was “control of work pacing” (alpha 0.46). Intrinsic motivation positively correlated with all the scales of organizational module, apart from inequality. Within this module, the degree of extrinsic motivation correlated with the support from the superior and coworkers, with fair leadership and human resources primacy. A negative correlation appeared with inequality. Conclusion. The general Nordic Questionnaire can be applied to a great extent to the conditions in our country.  Our study shows a low consistency of the scales learning job demands, control of decision, control of work pacing, so the questions in them should be adjusted to the conditions in our country. Extrinsic motivation resulted in higher values than the values of intrinsic motivation in our workers, which is opposite to the results of the original questionnaire.
Keywords: job satisfaction; medical staff; questionnaires; serbia